Pengaruh Literasi Keuangan Terhadap Kinerja Petani Padi Sawah di Kecamatan Pamona Puselemba Kabupaten Poso - Guampe, Feliks Arfid; Olvit Olniwati Kayupa; Septian Aditya Kolompo (Lembaga Pengembangan Kinerja Dosen, 2024)
Agriculture is a crucial sector in development because it serves as the primary sector for meeting national food needs and security. Due to its significant role, farmers as the main actors in agriculture need to possess good financial literacy, which ultimately impacts the performance of agricultural businesses. Therefore, the purpose of this study is to examine the impact of financial literacy on the performance of rice farmers. This study was conducted in Pamona Puselemba District, Poso Regency. The researcher used a quantitative approach with a survey method. The sample size of the study was 100 rice farmers, obtained using simple random sampling technique from a population of 2,226. Simple regression was used as the data analysis technique. The results of the study indicate that financial literacy has a positive and significant impact on the performance of rice farmers. Thus, financial literacy plays an important and multidimensional role in enhancing the performance of rice farmers.